(untitled) (Research, Society and Development, 2020)
Objective: To report the use of gerontotechnologies with a group of elderly people in a Basic Health Unit (UBS) located in Belém-PA. Methodology: It is a descriptive work, with a qualitative approach of the type of experience report, carried out in May 2019, by the members of the Academic League of Nursing in Health of the Elderly (LAESI). The strategies used involved gerontotechnologies in a playful way, including "attention games", "dance in color", "memory game", "puzzle", "stick game" and "adding and playing". Results and discussion: During the use of these gerontotechnologies, it was noticed that there was acceptance of the proposed methodology evidenced by the active participation of the elderly. The applicability of technologies aimed at the elderly helps to maintain quality of life in the senescence period, allowing the identification of possible risk factors that include the decline in cognition, memory, visual perception and mobility. This makes it possible to establish interventions to avoid irreversible complications in the life of the elderly. Final considerations: It was observed that the observed benefits could be better if there were constant activities aimed at the elderly with the use of gerontotechnologies in primary care, working crucially in promotion and health.